2022
DOI: 10.48550/arxiv.2205.13715
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vetting the Lobster Diagram: Searching for Unseen Companions in Wide Binaries using NASA Space Exoplanet Missions

Zachary Hartman,
Sébastien Lépine,
Ilija Medan

Abstract: Over the past decade, the number of known wide binary systems has exponentially expanded thanks to the release of data from the Gaia Mission. Some of these wide binary systems are actually higherorder multiples, where one of the components is an unresolved binary itself. One way to search for these systems is by identifying overluminous components in the systems. In this study, we examine 4947 K+K wide binary pairs from the SUPERWIDE catalog and quantify the relative color and luminosity of the components to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…A sample of 392 resolved triple systems was also selected from Gaia by Tokovinin (2022). Hartman et al (2022) examined a sample of resolved K+K binaries, and found at least 40 per cent to be hierarchical triple systems with an unresolved inner binary.…”
mentioning
confidence: 99%
“…A sample of 392 resolved triple systems was also selected from Gaia by Tokovinin (2022). Hartman et al (2022) examined a sample of resolved K+K binaries, and found at least 40 per cent to be hierarchical triple systems with an unresolved inner binary.…”
mentioning
confidence: 99%